2015
DOI: 10.1021/jacs.5b00106
|View full text |Cite
|
Sign up to set email alerts
|

Redirection of Genetically Engineered CAR-T Cells Using Bifunctional Small Molecules

Abstract: Chimeric antigen receptor (CAR)-engineered T cells (CAR-Ts) provide a potent antitumor response and have become a promising treatment option for cancer. However, despite their efficacy, CAR-T cells are associated with significant safety challenges related to the inability to control their activation and expansion and terminate their response. Herein, we demonstrate that a bifunctional small molecule "switch" consisting of folate conjugated to fluorescein isothiocyanate (folate-FITC) can redirect and regulate F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(137 citation statements)
references
References 28 publications
0
137
0
Order By: Relevance
“…To redirect the specificity of CAR-T cells with a switch molecule, we first generated CAR-T cells that bind the synthetic dye, fluorescein (FITC), which is physiologically absent and has demonstrated excellent selectivity in imaging agents and in antibody or smallmolecule-based switch designs (18,20,23). We generated CAR-T cells using a range of anti-FITC scFv sequences that differ in their affinities toward FITC (24)(25)(26)(27), and found that all anti-FITC CAR-T cells elicit in vitro cytotoxicity with the same switch (vide infra) to a similar extent (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To redirect the specificity of CAR-T cells with a switch molecule, we first generated CAR-T cells that bind the synthetic dye, fluorescein (FITC), which is physiologically absent and has demonstrated excellent selectivity in imaging agents and in antibody or smallmolecule-based switch designs (18,20,23). We generated CAR-T cells using a range of anti-FITC scFv sequences that differ in their affinities toward FITC (24)(25)(26)(27), and found that all anti-FITC CAR-T cells elicit in vitro cytotoxicity with the same switch (vide infra) to a similar extent (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of switches used in this approach include TAA-specific monoclonal antibodies that elicit antitumor activity from Fc-specific CAR-T cells (17), and chemically or enzymatically modified antibody-hapten conjugates that redirect antihapten CAR-T cells (18,19). Recently, we have demonstrated the redirection of anti-FITC CAR-T cells with a heterobifunctional small-molecule switch, folate-FITC, which selectively targets folate receptor-overexpressing cancers (20). Although these reports established the feasibility of eliciting an anticancer response with switchable CAR-T (sCAR-T) cells, it has yet to be shown whether the efficacy of sCAR-T cells is comparable to current CAR-T cell therapies in the clinic.…”
Section: Significancementioning
confidence: 99%
“…Such molecules mediate the binding between antigen and CAR, for example, a linker consisting of folate conjugated to fluorescein isothiocyanate (folate-FITC) can redirect and regulate FITC-specific CAR T cell activity toward folate receptor)-overexpressing tumour cells. 64 Finally, CAR T cells have been engineered that have split receptors, in which antigenbinding and all necessary intracellular signalling components assemble only in the presence of a titratable small molecule. 65 Regardless of the mechanism, on or off switches add in vivo control over CAR T cell function and potentially enhance safety.…”
Section: 61mentioning
confidence: 99%
“…In an alternative approach, the CAR binds to a protein epitope, which is not encoded by the human genome and which is linked to cancer-targeting antibodies [54]. In another example, folate receptor-positive cancer cells were marked by a fluorescein isothiocyanate (FITC)-conjugated folate which binds to the cancer cells and is recognized by a FITC-specific CAR [55,56]. By using more than one FITC-labeled molecule which mark the cancer cells, the same CAR T cell can target multiple types of cells within the tumor lesion.…”
Section: Cars With Exchangeable Antigen Recognitionmentioning
confidence: 99%